ASPEK TEKNIK DAN KELAYAKAN USAHA PENGERINGAN IKAN TERI (Stolephorus sp) DI DESA AMBESIA SELATAN KECAMATAN TOMINI KABUPATEN PARIGI MOUTONG SULAWESI - Emma Sosiawati (Fakultas Pertanian Universitas Alkhairaat Palu, 2019)
This research aims to find out anchovy drying technique (Stolephorus sp.) and the feasibility of anchovy drying business (Stolephorus sp.) in South Ambesia village of Tomini district of Parigi Moutong regency of Central Sulawesi Province. Data collections in this research were interview technique, observation, and active participation of the writer along with the fish preservation business owner in South Ambesia village of Tomini district. The data were processed by qualitative and quantitative descriptive analysis. The research results show that in technically and economically, the effort to dry anchovy (Stolephorus sp) was feasible to be developed. Economic analysis for the calculation of overall net income of 5 respondents amounting to Rp.188,295,100 per year, if the respondent per fisherman is counted, a yearly net income of Rp. 37,659,020, and converted 12 months (1 year) the value reached Rp. 3,138,251 per month. While the feasibility analysis of the anchovy drying business obtained a Benefit Cost Ratio of 2.10